An Integration of BSC and AHP for creating VOE’s Barriers of Entry Strategy - Ubed, Roby Syaiful; Raharjo, Taufik (Goodwood Publishing, 2024)
Purpose: The aim of this study is to create social constructs related to Village-owned Enterprise (VOE) performance measurement tools and establish a hierarchy of strategy formulation using the Analytical Hierarchy Process (AHP). Research Methodology: The methods used in this research were interviews, observations, and literature reviews to gain overall information to achieve the research goals. The purposively chosen sample was PH Village and PL VOE in Yogyakarta Province. Based on the data obtained, a BSC simulation was conducted, followed by strategic analysis using AHP. Results: This study established a social construct of VOE’s performance measurement model based on the social enterprise BSC introduced by Bull (2007) and Somers (2005). A simulation was conducted by measuring the performance of the PL VOE. A total score of 96,49% was obtained for the PL performance measurement result. In addition, a strategy to create barriers to entry was established in this study. The analysis showed that the product differentiation strategy had the highest score (0,66394). To obtain the strategy, the village head, as a village vision creator, must create vision (0,47037) focusing on how to satisfy the PL’s consumers (0,35131). Limitations: The limitation of the research is the lack of an observable sample since not all the villages and VOEs have the required data for research purposes. Contribution: The benefit of this study is that it focuses on the Yogyakarta Provincial Village Community Empowerment Service. This research can be used to formulate strategic policies for the Yogyakarta Provincial government to improve VOE performance, mainly in terms of barriers to entry creation. Novelty: This study contributes to the strategic management of social enterprises in Indonesia, particularly VOE. The use of social BSC and AHP in one article to measure the performance of VOE and to create barriers to entry strategies is still scarce in Indonesia.